Beyond life: systematic review of frontier zones in digital immortality - Galvão, Vinícius Ferreira; Maciel, Cristiano; Pereira, Vinicius Carvalho (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2022: Anais do XXI Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2022)
Technological advancements offer nowadays opportunities of using deceased users’ data to create websites ou social media pages to homage them, or forwarding those data to heirs. There are also attempts of producing digital immortality - the possibility to use posthumous data to bring the dead "back to life" via chatbots or avatar robots. Such topic has gotten increased attention from the academic community due to the variety of technical, social and cultural perspectives from which this topic can be analyzed. In such a vast scenario, this paper is an attempt to answer the following question: What research topics are being discussed concerning digital immortality in the academic community? We carried out a Systematic Review (SR) comprising papers published in the last 10 years (2011-2021), focusing on digital immortality, derived from studies that address both human and technical aspects of the subject. In the SR protocol, we formulated search strings relating to the topic, and they were inserted in the Google Academic search engine. The articles found were read, tabulated and categorized based on themes they had in common. The results show what points have been more addressed by scholars, and what themes still need to be further explored.